The formulation of edamame flour and tuna fish protein hydrolyzate biscuit as an alternative supplementary feeding for stunting - Rachmawati, Septi Nur; Antika, Ruli Bahyu; Rohmawati, Ninna; Hermilasari, Rista Dwi (Alma Ata University Press, 2025)
ABSTRAKLatar Belakang: Stunting keadaan kurang gizi paling umum yang terjadi di Indonesia dan masih menjadi permasalahan yang harus ditangani saat ini. Salah satu upaya untuk memperbaiki kondisi stunting pada balita yaitu dengan memenuhi kebutuhan protein melalui PMT yang tinggi protein. Biskuit dapat menjadi salah satu media dalam perbaikan zat gizi apabila ditambahkan dengan bahan tertentu. Pangan lokal yang dapat ditambahkan dalam bahan pembuatan biskuit adalah kacang kedelai edamame yang dioah menjadi tepung edamame dan ikan tuna yang dijadikan hidrolisat protein ikan (HPI).Tujuan: Tujuan dari penelitian ini adalah untuk mengetahui formulasi terbaik dari biskuit tepung edamame dengan tambahan HPI tuna untuk memperbaiki kondisi stunting pada balita.Metode: Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) faktor tunggal dengan tiga sampel, yaitu perbandingan formulasi tepung edamame dengan HPI tuna dengan 3 taraf (F1 30:10, F2 25:15, dan F3 20:20). Penelitian dimulai dengan pembuatan tepung edamame, HPI tuna, dan biskuit tepung edamame dan HPI tuna. Selanjutnya biskuit tepung edamame dan HPI tuna diuji organoleptik yang meliputi kesukaan warna, rasa, aroma, tekstur, dan keseluruhan pada 25 panelis semi terlatih. Formulasi terpilih akan dianalisis kadar protein, lemak, dan karbohidrat.Hasil: Berdasarkan uji organoleptik dan total hasil pembobotan didapatkan bawah formulasi biskuit terpilih adalah F3. Hasil uji Kruskal Wallis menunjukkan bahwa penambahan tepung edamame dan HPI tuna berpengaruh nyata terhadap kesukaan warna (p<0,05). Berdasarkan uji laboratorium diketahui jika formula biskuit terpilih (F3) memiliki kandungan gizi per 100 gram: protein 16,81±0,07 gram; lemak 19,66±0,14 gram; karbohidrat 49,05±0,06 gram.Kesimpulan: Penelitian ini menunjukkan bahwa formulasi biskuit terpilih adalah F3 dengan kandungan tepung edamame 20% dan HPI tuna 20%. Kandungan protein dan lemak pada biskuit terpilih (F3) lebih tinggi dibandingan dengan biskuit PMT Pabrikan. KATA KUNCI: biskuit; hidrolisat protein ikan; ikan tuna; tepung edamame; stuntingABSTRACTBackground: Stunting is the most common malnutrition condition that occurs in Indonesia and is still a problem that has to be solved today. One of the efforts to improve stunting conditions in toddlers is by fulfilling the protein needs through supplementary feeding which has high protein. Biscuits can be a medium for improving nutrition if they are added with certain ingredients. Local foods that can be added to biscuits are edamame soybeans which are processed into edamame flour and tuna which is made into fish protein hydrolyzate (FPH).Objectives: To find out the best formulation of edamame flour biscuits with the addition of tuna FPH to improve stunting conditions in toddlers.Methods: This research used a single factor Completely Randomized Design (CRD) with three samples, which were a comparison of edamame flour formulation with tuna FPH with 3 levels (F1 30:10, F2 25:15, and F3 20:20). The research began with making edamame flour, FPH tuna, and the biscuits. Furthermore, edamame flour and tuna FPH biscuits were tested organoleptically which included color, taste, aroma, texture, and overall preferences of 25 semi-trained panelists. The selected formulation will be analyzed for protein, fat, and carbohydrate levels.Results: Based on organoleptic tests and the total weighting results obtained the selected biscuit formulation was F3. The results of the Kruskal Wallis test showed that the addition of edamame flour and tuna FPH had a significant effect on color preference (p<0.05). Based on laboratory tests, it is known that the selected biscuit formula (F3) has nutritional content per 100 grams: protein 16.81±0.07 g; fat 19.66±0.14 g; carbohydrate 49.05±0.06 gConclusions: The selected biscuit formulation is F3 with 20% edamame flour content and 20% tuna FPH. The protein, fat, and carbohydrate content of the selected biscuits (F3) is higher than the supplementary feeding manufactured biscuits. KEYWORD: biscuit; edamame flour; fish protein hydrolyzate; stunting; tuna